EKSPERIMENTASI PEMBELAJARAN MATEMATIKA DENGAN MODEL KOOPERATIF TIPE NHT DAN TPS TERHADAP PRESTASI BELAJAR DAN MOTIVASI BERPRESTASI SISWA DITINJAU DARI KECERDASAN EMOSIONAL POKOK MATERI PERSAMAAN LINEAR SATU VARIABEL PADA SISWA SMP NEGERI DI KOTA SURAKARTA - Aspriyani, Riski; Mardiyana, Mardiyana; Sari S, Dewi Retno (Jurnal Pembelajaran Matematika, 2014)
Abstract: This research was aimed to know: (1) which gave achievement and motivation to do better, students who were subjected to cooperative models of NHT, TPS, or Conventional and students with high, medium, or low emotional intelligence; (2) on each model of learning and at each category of emotional intelligence which provided achievement and motivation to do better. The population was all the students of VII grade of Junior High Schools in Surakarta year of 2013/2014 and obtained a sample of 266 students. The instruments used was achievement test, motivation, and emotional intelligence questionnaire. Test requirements analysis included a multivariate normality and the variance-covariance homogeneity test. Balance test used a unbalanced one way multivariate and hypothesis testing used unbalanced two way multivariate. The results of research were: (1a) students subjected to NHT gave as good as the achievement of TPS but better than Conventional, and TPS provided a better achievement than Conventional. As well students subjected to NHT, TPS, and Conventional gave the same motivation, (1b) students with high emotional intelligence provided as good learning achievement as the students with moderate and low emotional intelligence. As well students who have high emotional intelligence gave better motivation than medium or low emotional intelligence but students with medium emotional intelligence provided as good motivation as the students with low emotional intelligence; (2ai) in each learning model, students with high, medium, and low emotional intelligence gave the same achievement, (2aii) in NHT model, students with high emotional intelligence gave as good as the motivation of students with medium emotional intelligence. As well students with high and medium emotional intelligence gave motivation better than low emotional intelligence, (2aiii) in TPS model, students with high emotional intelligence gave motivation better than medium and low emotional intelligence but students with medium emotional intelligence gave as good motivation as students with low emotional intelligence, (2aiv) in Conventional model, students with high, medium, and low emotional intelligence gave the same motivation, (2bi) in each category of emotional intelligence, NHT gave as good as the achievement of TPS, but NHT and TPS gave better achievement than Conventional, (2bii) at high emotional intelligence, students subjected to NHT gave as good as the motivation of TPS, but NHT and TPS better than Conventional, (2biii) at medium and low emotional intelligence, students subjected to NHT, TPS, and Conventional gave the same motivation.Keywords: NHT, TPS, emotional intelligence, learning achievement and achievement motivation